Crystal structures and phase transitions in Ba2HoTaO6 - Kennedy, B; Saines, P; Kubota, Y; Minakata, C; Hano, H; Kato, K; Takata, M (2007)
The structure of the cation-ordered double perovskite Ba2HoTaO6 was examined using synchrotron X-ray powder diffraction at fine temperature intervals over the range of 90-300 K. Ba2HoTaO6 has a cubic structure in space group F m over(3, ̄) m at room temperature. A proper ferroelastic phase transition to I4/m tetragonal symmetry occurs near approximately 260 K. Analysis of the spontaneous tetragonal strain versus temperature indicated that the phase transition is second order in nature. © 2007 Elsevier Ltd. All rights reserved.